2019
DOI: 10.1111/jvs.12766
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation reduction alters herbaceous community structure and composition in a savanna

Abstract: Questions In the changing climate scenario, the decline in precipitation is expected to alter water availability for plants, which in turn affects plant community structure and composition. The responses of community composition and structure to declines in precipitation are well documented in other biomes but remain understudied in water‐limited savannas. Location A savanna ecosystem in southwest China. Methods We used a four‐year (2014–2017) precipitation manipulation experiment to examine changes in herbace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 62 publications
0
5
0
1
Order By: Relevance
“…This result could be attributed to the fact that annual weeds may be rapid growth species with a short life span, growing and reproducing faster than perennials when encountering disadvantageous conditions like drought [35]. Overall, the present study found contrasting results of the relative abundance of weed types under different crop residues management, indicating that different weed types may have different adaptation strategies associated with their morphological or physiological traits to adapt to environmental changes [36].…”
Section: Effects Of Crop Residues Retention On the Weed Community Diversitymentioning
confidence: 59%
“…This result could be attributed to the fact that annual weeds may be rapid growth species with a short life span, growing and reproducing faster than perennials when encountering disadvantageous conditions like drought [35]. Overall, the present study found contrasting results of the relative abundance of weed types under different crop residues management, indicating that different weed types may have different adaptation strategies associated with their morphological or physiological traits to adapt to environmental changes [36].…”
Section: Effects Of Crop Residues Retention On the Weed Community Diversitymentioning
confidence: 59%
“…Numerous studies in grasslands documented shifts in plant species abundances in response to natural or experimental drought (Albertson & Weaver, 1942; Breman & Cissé, 1977; Gibbens & Beck, 1987; Hoover et al, 2014; Jin et al, 2019), either by reordering of species or functional groups (i.e., some species become abundant under changing conditions at the expense of others; Smith et al, 2009), or through the replacement of a dominant species. When a shift in species abundances occurs, the litter decomposition rate of species that are favored under altered environmental conditions may differ from that of previously abundant species.…”
Section: Discussionmentioning
confidence: 99%
“…The extinction risk of woody and herbaceous species was positively and negatively correlated with MAP, respectively. At the same time, herbaceous communities in dry grassland ecosystems are particularly vulnerable to climate change, which can reduce competition for invasive species (Baird et al, 2021), and further negatively affect populations of native, threatened herbaceous species (Jin et al, 2019). For woody plants experiencing the effects of climate warming, boreal forests are example ecosystems that may be particularly sensitive to rising temperatures (Babst et al, 2019).…”
Section: Discussionmentioning
confidence: 99%